Program Pendampingan Literasi, Numerasi, Administrasi dan Adaptasi Teknologi di SMPN Satap 4 Suela Kabupaten Lombok Timur - Hendri, Wira; Komala, Rina (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Education inequality is one of the problems for the government in educating the nation’s life. Education that should be enjoyed by all levels of society has not been implemented optimally in accordance with what is mandated by law. The Independent Campus Learning Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. The Teaching Campus Program is one of the programs in the Merdeka Learning Campus Program which aims to teach and assist with technology adaptation, school administration, and teachers. One of the schools targeted by the Teaching Campus program is SMPN SATAP 4 SUELA which is located in Lekong Pulut Hamlet, Mekar Sari Village, Suela District, East Lombok Regency. In the Teaching Campus program, lecturers and students who are appointed to take part in the program have the responsibility of assisting the school in the teaching process, assisting with adaptation to technology, and assisting with school administration. In addition, Teaching Campus students have the responsibility of improving student character, increasing student literacy and numeracy, and increasing student learning motivation.